Associations between physical activity and health-related fitness: Differences across childhood - Zeinab Khodaverdı; Jacqueline Goodway; David Stodden (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to evaluate associations between physical activity (PA) intensities to aspects of health-related physical fitness (HRPF) across childhood (4-11 years). A sample of 160 children, including 4-5 years (n=55), 7-8 years (n=60), and 10-11 years (n=45) old, participated in this study. Five day PA levels (light, moderate, and vigorous) were measured using accelerometry. HRPF was assessed using curl-ups (abdominal strength/endurance), pushups (upper body strength/endurance), PACER (cardiorespiratory fitness) and grip strength. Hierarchical and linear multiple regression analysis quantified associations between HRPF components and PA levels across childhood. After controlling for BMI and age, cardiorespiratory fitness accounted for 3% of variation in vigorous in PA in 4-11 year-old children and significantly predicted 23% of variance in vigorous PA in late childhood. No other statistically significant associations between any aspect of fitness and any PA intensities were noted across age groups. These results support other research suggesting cardiorespiratory fitness may be the only aspects of HRPF that is related to various intensities of PA (as assessed via accelerometry), across childhood. An important implication of this study is that physical education should provide an equal emphasis on developing PA habits and HRPF as both are independently associated with health in childhood.